Adaptation and validation of the social skills scale for intercultural primary school pupils - Aranda-Vega, Eva María; Ortiz-Marcos, José Manuel; Tomé-Fernández, María (Frontiers in Education, 2023)
In recent decades, large migratory movements have been taking place, which has turned Spain into a culturally diverse country. For this reason, the present research focuses on social skills, which are considered of utmost importance in different educational contexts. To this end, the aim was to adapt and validate a scale to diagnose social skills in young people aged 6 to 12 years (M = 9.65 years; SD = 1.395). Of these, 460 (60.4%) were boys and 301 (39.60%) girls. For this purpose, a methodology is followed that involves the judgement of experts in the field, followed by an exploratory factor analysis (EFA) and then a confirmatory factor analysis (CFA). The sample chosen for the study is made up of 1564 young people, Primary School students from different Andalusian localities that constitute border cities in the south of Spain, and which have a great cultural, ethnic and religious diversity that is reflected in their classrooms. The items of the scale were obtained from relevant questionnaires on the subject under study, initially containing 33 items and 6 underlying constructs. After validation of the AFE (n = 761), the structure is verified and the model is corroborated by CFA (n = 803) with structural equations (RMSEA = 0.04; CFI = 0.77; TLI = 0.73). Finally, the reliability and internal consistency of the instrument is examined, obtaining values above 0.6 for all dimensions. As a result, a new scale composed of 33 items and 5 dimensions is obtained, with psychometric properties that give it validity and reliability. In conclusion, we present a useful resource for teachers that allows them to diagnose the social skills of Primary School students in schools characterised by their great cultural diversity and among the peer group.